Peran Organisasi Ketua Karang Taruna Dalam Membangun Solidaritas Pemuda Chandra Baru RW 017 - Aloysius Faby Sukmawardi; Yudha Febri Al Paksi; Murtiadi Murtiadi (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
The purpose of this study was to determine the pattern of organizational communication in Karang Taruna Komplek Chandra Baru Rw17. The data collection technique in this study used purposive sampling technique which was obtained by conducting interviews with 2 Youth Organization administrators and filling out questionnaires to several Youth Organization administrators. The analysis method is qualitative analysis without using statistical analysis. Karang Taruna Rw 017 has prioritized solidarity, interesting programs, member development, good organizational culture, and responsibility for the surrounding environment. However, there are several problems that can hinder Karang Taruna in completing its responsibilities, so efforts need to be made to overcome these problems.